The competitiveness of future specialists of pharmacy in the professional training process: results of experimental work on motivation criterion - Moroz, G. (Scientific notes of the pedagogical department, 2021)
The relevance of this problem is explained by the need of training of pharmacy specialists who are competitive in the labor market. Their main features are the fundamental level of professional training, formed subject and general competences, the ability to make decisions in difficult situations. The purpose of the research: to highlight the content of the model of increasing the competitiveness of future pharmacy specialists in the process of professional training. The task of the research: to clarify the essence of the concept of “competitiveness of a specialist”; to focus on the specifics of the content of the definition of “competitiveness of a pharmacy specialist”; a brief characterization of the stages of introducing a model of increasing the competitiveness of a pharmacy specialist (motivational-objective, procedural, result-evaluative); to cover the results of experimental work on the motivational criterion. Research methods: theoretical ones - an analysis of sources to characterize the state of development of the problem indicated by us; modeling - for the characterization of the components of the model of increasing the competitiveness of future specialists in pharmacy and the criteria for its formation; empirical ones - questioning, testing, supervision - to identify the levels of formation of students' competitiveness; methods of mathematical statistics - for quantitative and qualitative analysis of the processing of empirical data; pedagogical experiment method - to test the effectiveness of the model of increasing the competitiveness of future specialists in pharmacy. The results of the study are giving us a chance to draw the following conclusions: the essence of the concept of “competitiveness of a specialist” is considered by us as the ability to compete, which determines the achievement of the best results by a person through the use of his personal and professional qualities in competition in the labor market”; the specificity of the content of the definition “competitiveness of a pharmacy specialist” is determined through the specifics of acquiring knowledge and professional experience in the process of professional training in the chosen specialty; the increasing of the competitiveness of a pharmacy specialist is possible due to the introduction of a specific model, which consists of a number of sequential and interdependent stages: motivational-objective, procedural, result-evaluative; the results of experimental work on the motivational criterion indicate the effectiveness of the methods of increasing the competitiveness of pharmaceutical students introduced by the author.